Improved students’ level of achievement, autonomy of learning, and metacognitive strategies through teaching social studies using new media - Lozanta, Alfredo A. Jr (Alipato : a Journal of Basic Education, 2021)
Access online through this link: https://journals.upd.edu.ph/index.php/ali/article/view/8577